A multi-scale structure composite strengthened high entropy alloy and preparation method thereof

By introducing multi-scale structures into high-entropy alloys, including micron-scale Laves phase, nano-scale HCP phase and atomic SRO structure, the problems of compressive and tensile strength imbalance in existing high-entropy alloys are solved, and the dual improvement of strength and elongation is achieved.

CN116516227BActive Publication Date: 2025-03-11QIQIHAR UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310261250.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-03-11
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

While the existing high-entropy alloys increase the compressive strength, the tensile strength is reduced, and the precipitation phase scale is single, which limits the strengthening effect and leads to the alloy being prone to hard and brittle fracture.

Method used

By introducing multi-scale structures, including micro-scale Laves phase, nano-scale HCP phase and atomic SRO structure, we build a composite microstructure, and combine annealing treatment and water quenching and other processes to optimize the microstructure of the alloy.

Benefits of technology

The yield strength and ultimate strength of the alloy are significantly improved, with the strength increased by more than 50%, while maintaining a high elongation rate, solving the performance balance problem between compressive and tensile strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116516227B_ABST
    Figure CN116516227B_ABST
Patent Text Reader

Abstract

The present invention is applicable to the technical field of high entropy alloys, and provides a multi-scale organization composite strengthening type high entropy alloy, which is composed of elements Co, Cr, Fe, Ni, Nb, and Mo, and the general formula in terms of atomic ratio is CoCrFeNiNbxMo0.4-x, wherein x=0.1-0.3; under the cast condition, the CoCrFeNiNbxMo0.4-x high entropy alloy is organized into an FCC matrix and a micron-sized Laves phase structure; after annealing, the CoCrFeNiNbxMo0.4-x high entropy alloy includes an FCC matrix, a micron-sized Laves phase, and an atomic-level SRO structure. The present invention also provides a method for preparing a multi-scale organization composite strengthening type high entropy alloy, comprising the following steps: according to the target atomic ratio, metal particles Co, Cr, Fe, Ni, Nb, and Mo are smelted to obtain a cast alloy; the cast alloy is annealed and quenched with water to obtain the multi-scale organization composite strengthening type high entropy alloy, and the annealing temperature is 600-800°C. The present invention constructs a composite microstructure of multi-scale precipitation phases and short-range order, and improves the yield strength and ultimate strength of the alloy while ensuring a certain plasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high entropy alloys, and in particular relates to a multi-scale structure composite reinforced high entropy alloy and a preparation method thereof. Background Art

[0002] High entropy alloys have shown excellent properties under various extreme conditions, such as high and low temperature strength, corrosion resistance, and radiation resistance. Among them, high entropy alloys with face-centered cubic structure have high ductility but relatively low yield strength, and are considered to be a good basis for further strengthening. Therefore, improving the strength of face-centered cubic high entropy alloys has been a research hotspot in recent years. The strength of face-centered cubic high entropy alloys can be improved by adopting strengthening mechanisms such as fine grain, work hardening, precipitation strengthening, and short range order (SRO) organization. In particular, precipitation-strengthened high entropy alloys have excellent mechanical properties and unique deformation behaviors, which have attracted great attention. For example, alloying Al, Ti, Nb, and Mo into CoCrFeNi face-centered cubic high entropy alloys can improve strength, but at the cost of reduced plasticity. In addition, it has been observed that refractory alloying elements such as Nb, Mo, V, Ta, and W make high entropy alloys more suitable for high temperature applications, but reduce their tensile strength while improving compressive strength. This may be due to the relatively large precipitates in these high entropy alloys, which limit the strengthening effect of the precipitates. Therefore, achieving a performance balance between compressive and tensile strength for wider applications is one of the challenges facing researchers.

[0003] In summary, in the existing alloy system, single alloying elements such as Al, Ti, Nb, Mo, Y, Ta, etc. are mostly used to alloy the CoCrFeNi face-centered cubic high entropy alloy, that is, Co, Cr, Fe, Ni and other alloying elements are melted in a vacuum arc melting furnace, and the precipitated phases of the obtained alloys are all single micron-scale intermetallic compounds. There is no obvious phase relationship between the precipitated phases and the matrix, which greatly weakens the plasticity of the alloy while improving the strength. If these hard and brittle compounds are not properly controlled, the alloy will become hard and brittle, and the metal pattern will break before reaching or just reaching the yield stage. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a multi-scale structure composite strengthened high entropy alloy, aiming to solve the problems raised by the above background technology.

[0005] The embodiment of the present invention is implemented as follows: a multi-scale structure composite strengthening high entropy alloy, the high entropy alloy is composed of the elements Co, Cr, Fe, Ni, Nb, and Mo, and the general formula of the high entropy alloy in terms of atomic ratio is CoCrFeNiNb x Mo 0.4-x, wherein x=0.1-0.3;

[0006] In the cast condition, CoCrFeNiNb x Mo 0.4-x The microstructure of high entropy alloy is FCC matrix and micron-scale Laves phase structure;

[0007] After annealing, CoCrFeNiNb x Mo 0.4-x The high entropy alloy includes FCC matrix, micron-scale Laves phase and atomic-scale SRO structure.

[0008] Another object of the embodiment of the present invention is to provide a method for preparing a multi-scale structure composite reinforced high entropy alloy, comprising the following steps:

[0009] According to the target atomic ratio, metal particles Co, Cr, Fe, Ni, Nb, and Mo are melted to obtain a cast alloy;

[0010] The cast alloy is annealed and quenched with water to obtain the multi-scale structure composite reinforced high entropy alloy, wherein the annealing temperature is 600-800°C.

[0011] Preferably, in the step of annealing the cast alloy, the annealing temperature is 700-800°C.

[0012] Preferably, the cast alloy is annealed at 700-800° C. to obtain a multi-scale composite reinforced high entropy alloy having a microstructure of an FCC matrix, a micron-scale Laves phase, a nano-scale HCP phase and an atomic-scale SRO structure.

[0013] Preferably, before the step of smelting the metal particles Co, Cr, Fe, Ni, Nb, and Mo, a step of deoxidizing with a Ti ingot under the protection of an argon atmosphere is included.

[0014] Preferably, in the step of smelting the metal particles Co, Cr, Fe, Ni, Nb, and Mo, the purity of the metal raw materials is 99.9%.

[0015] Preferably, in the step of smelting the metal particles Co, Cr, Fe, Ni, Nb, and Mo, the smelting is specifically to melt the metal particles into button ingots, turn them over after cooling, and repeat the smelting for more than 5 times.

[0016] A multi-scale organization composite strengthened high entropy alloy provided in an embodiment of the present invention solves the problem that the precipitation phase of the alloy system in the prior art is single and coarse, and there is no obvious phase relationship between the precipitation phase and the matrix, the strengthening effect is limited, and the metal plasticity is greatly weakened, and the metal strength is difficult to be fully exerted, that is, brittle fracture occurs. The multi-scale organization is constructed by inducing multi-scale precipitates and SRO to construct a composite microstructure of multi-scale precipitation phases and SRO, and the yield strength and ultimate strength of the alloy are improved under the condition of ensuring a certain plasticity. After the composite alloying of Nb and Mo elements, a micron-sized second phase is generated in the matrix. The second phase presents a eutectic structure with the matrix and precipitates in lamellar form. After annealing, the final alloy is obtained. Dense nanoscale precipitated phases and atomic-level SRO are generated in the alloy matrix. At the same time, large lamellar structures are reduced and turned into irregular strips. After annealing, the yield strength and ultimate tensile strength of the cast alloy can reach 751MPa and 1.1GPa, with a strength increase of more than 50%. At the same time, the elongation of 15.14% can be maintained, and the elongation is only reduced by 2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The cast CoCrFeNiNb provided in Example 1 0.1 Mo 0.3 Scanning image of high entropy alloy microstructure;

[0018] Figure 2 The cast and annealed CoCrFeNiNb provided in Example 1, Example 2 and Example 3 0.1 Mo 0.3 XRD pattern of high entropy alloy;

[0019] Figure 3 The CoCrFeNiNb annealed at 600°C provided in Example 1 0.1 Mo 0.3 Scanning image of high entropy alloy microstructure;

[0020] Figure 4 The CoCrFeNiNb annealed at 700°C provided in Example 2 0.1 Mo 0.3 Scanning image of high entropy alloy microstructure;

[0021] Figure 5 The CoCrFeNiNb annealed at 800°C provided in Example 3 0.1 Mo 0.3 Scanning image of high entropy alloy microstructure;

[0022] Figure 6 The CoCrFeNiNb provided in Example 2 0.1 Mo 0.3Transmission electron microscopy (TEM) analysis of high entropy alloy precipitation phase, where (a) is the morphology of the precipitation phase, (b) is the selected area diffraction spot of the precipitation phase, and (c) is the high-resolution image of the interface between the precipitation phase and the matrix;

[0023] Figure 7 CoCrFeNiNb provided in Example 1, Example 2 and Example 3 0.1 Mo 0.3 Transmission electron microscopy characterization of high entropy alloy spherical aberration;

[0024] Figure 8 A microstructure evolution diagram provided for an embodiment of the present invention;

[0025] Fig. 9 The cast and annealed CoCrFeNiNb provided in Example 1, Example 2 and Example 3 0.1 Mo 0.3 Tensile stress-strain curve of the sample made of high entropy alloy;

[0026] Fig.10 The CoCrFeNiNb annealed at 700°C provided in Example 4 0.2 Mo 0.2 Scanning image of high entropy alloy microstructure;

[0027] Fig.11 The CoCrFeNiNb annealed at 700°C provided in Example 4 0.2 Mo 0.2 Transmission image of high entropy alloy microstructure;

[0028] Fig.12 The CoCrFeNiNb annealed at 700°C provided in Example 5 0.3 Mo 0.1 Scanning image of high entropy alloy microstructure;

[0029] Fig.13 The CoCrFeNiNb annealed at 700°C provided in Example 5 0.3 Mo 0.1 Transmission image of high entropy alloy microstructure;

[0030] Fig.14 The cast and annealed CoCrFeNiNb provided in Example 4 0.2 Mo 0.2 Tensile stress-strain curve of the sample made of high entropy alloy;

[0031] Fig.15 The cast and annealed CoCrFeNiNb provided in Example 4 0.3 Mo 0.1 Tensile stress-strain curve of samples made of high entropy alloy. Implementation

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] A multi-scale structure composite strengthening high entropy alloy, the high entropy alloy is composed of the elements Co, Cr, Fe, Ni, Nb, and Mo, and the general formula of the high entropy alloy in terms of atomic ratio is CoCrFeNiNb x Mo 0.4-x , wherein x=0.1-0.3;

[0034] In the cast condition, CoCrFeNiNb x Mo 0.4-x The microstructure of high entropy alloy is FCC matrix and micron-scale Laves phase structure;

[0035] After annealing, CoCrFeNiNb x Mo 0.4-x High entropy alloys include FCC (Face Center Cubic) matrix, micron-scale Laves phase, and atomic-scale SRO structure;

[0036] The method for preparing the multi-scale structure composite reinforced high entropy alloy comprises the following steps:

[0037] (1) According to the above target atomic ratio, metal ingots Co, Cr, Fe, Ni, Nb, and Mo with a purity of 99.9% are placed in a vacuum arc melting furnace. Under the protection of argon atmosphere, the metal is deoxidized with a Ti ingot, and then the metal is melted. To ensure the uniformity of the melting, the metal particles are melted into button ingots, which are turned over after cooling. The melting is repeated for more than 5 times to obtain a cast alloy;

[0038] (2) Annealing the cast alloy at 600-800° C. for 24 hours and then quenching with water to obtain the multi-scale structure composite strengthened high entropy alloy.

[0039] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0040] Example 1: A multi-scale structure composite strengthened high entropy alloy (CoCrFeNiNb 0.1 Mo 0.3 A method for preparing a high entropy alloy comprises the following steps:

[0041] (1) Putting metal particles with a purity of 99.9% and an atomic ratio of Co:Cr:Fe:Ni:Nb:Mo=1:1:1:1:0.1:0.3 into a vacuum arc melting furnace, deoxidizing with a Ti ingot under the protection of an argon atmosphere, and then smelting the metal. To ensure the uniformity of the smelting, the metal particles are melted into button ingots, which are turned over after cooling, and the smelting is repeated for more than 5 times to obtain a cast alloy;

[0042] (2) The cast alloy was annealed at 600°C for 24 hours and then quenched with water to obtain the final alloy.

[0043] Example 2: A multi-scale composite reinforced high entropy alloy (CoCrFeNiNb 0.1 Mo 0.3 A method for preparing a high entropy alloy comprises the following steps:

[0044] (1) Putting metal particles with a purity of 99.9% and an atomic ratio of Co:Cr:Fe:Ni:Nb:Mo=1:1:1:1:0.1:0.3 into a vacuum arc melting furnace, deoxidizing with a Ti ingot under the protection of an argon atmosphere, and then smelting the metal. To ensure the uniformity of the smelting, the metal particles are melted into button ingots, which are turned over after cooling, and the smelting is repeated for more than 5 times to obtain a cast alloy;

[0045] (2) The cast alloy was annealed at 700°C for 24 hours and then quenched with water to obtain the final alloy.

[0046] Example 3: A multi-scale composite reinforced high entropy alloy (CoCrFeNiNb 0.1 Mo 0.3 A method for preparing a high entropy alloy comprises the following steps:

[0047] (1) Putting metal particles with a purity of 99.9% and an atomic ratio of Co:Cr:Fe:Ni:Nb:Mo=1:1:1:1:0.1:0.3 into a vacuum arc melting furnace, deoxidizing with a Ti ingot under the protection of an argon atmosphere, and then smelting the metal. To ensure the uniformity of the smelting, the metal particles are melted into button ingots, which are turned over after cooling, and the smelting is repeated for more than 5 times to obtain a cast alloy;

[0048] (2) The cast alloy was annealed at 800°C for 24 hours and then quenched with water to obtain the final alloy.

[0049] Example 4: A multi-scale composite reinforced high entropy alloy (CoCrFeNiNb 0.2 Mo 0.2 A method for preparing a high entropy alloy comprises the following steps:

[0050] (1) Putting metal particles with a purity of 99.9% and an atomic ratio of Co:Cr:Fe:Ni:Nb:Mo=1:1:1:1:0.2:0.2 into a vacuum arc melting furnace, deoxidizing with a Ti ingot under the protection of an argon atmosphere, and then smelting the metal. To ensure the uniformity of the smelting, the metal particles are melted into button ingots, which are turned over after cooling, and the smelting is repeated for more than 5 times to obtain a cast alloy;

[0051] (2) The cast alloy was annealed at 700°C for 24 hours and then quenched with water to obtain the final alloy.

[0052] Example 5: A multi-scale composite reinforced high entropy alloy (CoCrFeNiNb 0.3 Mo 0.1 A method for preparing a high entropy alloy comprises the following steps:

[0053] (1) Putting metal particles with a purity of 99.9% and an atomic ratio of Co:Cr:Fe:Ni:Nb:Mo=1:1:1:1:0.3:0.1 into a vacuum arc melting furnace, deoxidizing with a Ti ingot under the protection of an argon atmosphere, and then smelting the metal. To ensure the uniformity of the smelting, the metal particles are melted into button ingots, which are turned over after cooling, and the smelting is repeated for more than 5 times to obtain a cast alloy;

[0054] (2) The cast alloy was annealed at 700°C for 24 hours and then quenched with water to obtain the final alloy.

[0055] Alloy internal structure analysis and performance testing:

[0056] The microstructure of the cast alloy obtained in step (1) of Example 1 was scanned and the results were as follows: Figure 1 As shown, through Figure 1 It can be seen that after the composite alloying of Nb and Mo elements, a micron-sized second phase is generated in the matrix. The second phase and the matrix present a eutectic structure and precipitate in lamellar form. XRD test is performed on the cast alloy to identify the type of precipitated phase. The results are as follows: Figure 2 As shown, through Figure 2 It can be seen that the as-cast alloy consists of FCC matrix and Laves phase, and the Laves phase is a precipitation phase with a close-packed hexagonal structure of Fe2Nb type;

[0057] The final alloy obtained in Example 1 was subjected to XRD test to identify the type of precipitated phase, and the results were as follows: Figure 2 As shown, through Figure 2 It can be seen that the final alloy after annealing at 600℃ is composed of FCC matrix and Laves phase, and no new phase is detected. In order to further identify the type of precipitated phase, scanning electron microscopy test is carried out, and the results are as follows Figure 3 As shown, through Figure 3It can be seen that after annealing, the large lamellar structures in the alloy matrix are reduced and become irregular strips, and no other precipitated phases are found;

[0058] The final alloy obtained in Example 2 was subjected to XRD testing to identify the type of precipitated phase. The results are as follows: Figure 2 As shown, through Figure 2 It can be seen that the final alloy structure after annealing at 700℃ has two more diffraction peaks marked by five-pointed stars. It is identified that the new phase may be a close-packed hexagonal structure (HCP) phase. In order to further identify the type of precipitated phase, scanning electron microscopy test is carried out, and the results are as follows: Figure 4 As shown, through Figure 4 It can be seen that after annealing, dense nanoscale precipitation phases are generated in the alloy matrix, and at the same time, large lamellar structures are reduced and become irregular strips. In order to further characterize the nanoscale precipitation phases, the metal sample is analyzed by transmission electron microscopy. The results are as follows: Figure 6 As shown by Figure 6 (a) It can be seen that a large number of nano-scale precipitates have indeed precipitated in the matrix, which can improve the strength of the alloy. Figure 6 (b) It can be seen that the incident axis of the diffraction spot is [112(__)0], the crystal type of the precipitated phase is HCP structure, the lattice constant is a=0.4688nm, c=0.7483nm, Figure 6 (c) and its enlarged image show that the interplanar spacing of the matrix is ​​2.38 Å, and the interplanar spacing of the precipitated phase is 2.12 Å. The mismatch between the two is small, forming a semi-coherent interface. The semi-coherent interface has a better strengthening effect and can improve the tensile strength of the alloy.

[0059] The final alloy obtained in Example 3 was subjected to XRD test to identify the type of precipitated phase. The results are as follows: Figure 2 As shown, through Figure 2 It can be seen that the final alloy structure after annealing at 800℃ also has an additional diffraction peak marked by a five-pointed star. It is identified that the new phase may be a close-packed hexagonal structure (HCP) phase. In order to further identify the type of precipitated phase, scanning electron microscopy test was carried out, and the results were as follows: Figure 5 As shown, through Figure 5 It can be seen that after annealing, dense nanoscale precipitation phases are generated in the alloy matrix, while there are fewer large lamellar structures, and irregular strips are also formed. The SEM test results are consistent with the XRD results;

[0060] The final alloys obtained after annealing in Example 1, Example 2 and Example 3 were characterized by spherical aberration transmission electron microscopy. The results are as follows: Figure 7 As shown, Figure 7 (a) is the transmission high-resolution image of the final alloy of Example 1 in the

[112] incident direction. Figure 7(b) is the transmission high-resolution image of the final alloy of Example 2 in the

[112] incident direction. Figure 7 (c) is the transmission high-resolution image of the final alloy of Example 3 in the

[112] incident direction. The inset is the Fourier transform of the image. It can be seen that there is a weak diffraction disk between the (000) crystal plane and the (3(__)11) crystal plane, indicating that there are other ordered structures in the face-centered cubic matrix. The size of the diffraction disk exceeds the Bragg spot by about an order of magnitude, indicating that the corresponding coherent area in the actual space should be very small, with a size similar to the length of the SRO. The distribution of the SRO structure can be obtained by performing an inverse Fourier transform on the additional diffraction disk, as shown in Figure 2. Figure 7 As shown in the bright areas in (d), (e), and (f), it can be seen that the order degree of the final alloy of Example 1 is the highest. This is because the formation of SRO is driven by thermodynamics, and the overall free energy is reduced by forming bonds between specific atomic pairs. Therefore, at lower temperatures, the degree of SRO will be higher; In summary, there is an atomic-level SRO structure in the final alloy matrix obtained in Example 1, Example 2, and Example 3;

[0061] In summary, CoCrFeNiNb 0.1 Mo 0.3 Through the organization control of annealing treatment, high entropy alloys construct a multi-scale microstructure consisting of micron-scale Laves phase, nanoscale HCP phase and atomic-scale SRO structure. The microstructure evolution is as follows Figure 8 As shown, the microstructure is a single-scale Laves phase + matrix in the cast state, which changes to Laves phase + matrix + atomic-scale SRO after annealing at 600℃, and changes to matrix + micron-scale Laves + nanoscale HCP + atomic-scale SRO after annealing at 700℃ and 800℃;

[0062] The cast alloy obtained in step (1) of Example 1, the final alloy obtained in Example 1, the final alloy obtained in Example 2, and the final alloy obtained in Example 3 were respectively made into specimens and subjected to tensile tests to obtain tensile stress-strain curves, as shown in FIG. Fig. 9 As shown, according to Fig. 9 It can be seen that compared with the cast sample, the annealed CoCrFeNiNb 0.1 Mo 0.3 Due to the multi-scale microstructure, the high entropy alloy has obtained higher yield strength and tensile strength. After annealing at 700 °C (CoCrFeNiNb 0.1 Mo 0.3 The yield strength and ultimate tensile strength of high entropy alloys reached 751MPa and 1.1GPa respectively, with a strength increase of more than 50%, while maintaining an elongation of 15.14%, with an elongation reduction of only 2%;

[0063] The final alloy obtained in Example 4 was subjected to microstructure scanning, and the results were as follows: Fig.10 As shown, the transmission characterization is performed and the results are as follows Fig.11 As shown, according to Fig.10 , Fig.11 It can be seen that in addition to the Laves phase in the as-cast state, nanoscale precipitation phases are also generated in the matrix, thus forming multi-scale structural strengthening;

[0064] The cast alloy obtained in step (1) of Example 4 and the final alloy obtained in Example 4 were made into specimens respectively, and tensile tests were carried out to obtain tensile stress-strain curves, such as: Fig.14 As shown, according to Fig.14 It can be seen that after annealing at 700℃, CoCrFeNiNb 0.2 Mo 0.2 The ultimate tensile strength of the high entropy alloy was increased from 761 MPa in the cast state to 1.06 GPa;

[0065] The final alloy obtained in Example 5 was subjected to microstructure scanning, and the results were as follows: Fig.12 As shown, the transmission characterization is performed and the results are as follows Fig.13 As shown, according to Fig.12 , Fig.13 It can be seen that in addition to the Laves phase in the as-cast state, nanoscale precipitation phases are also generated in the matrix, thus forming multi-scale structural strengthening;

[0066] The cast alloy obtained in step (1) of Example 5 and the final alloy obtained in Example 5 were made into specimens, and tensile tests were performed to obtain tensile stress-strain curves, such as: Fig.15 As shown, according to Fig.15 It can be seen that after annealing at 700℃, CoCrFeNiNb 0.3 Mo 0.1 The ultimate tensile strength of the high entropy alloy was increased from 894 MPa in the cast state to 1.05 GPa;

[0067] In summary, the CoCrFeNiNb x Mo 0.4-x After annealing at a suitable temperature, the series of alloys construct a multi-scale microstructure consisting of micron-scale Laves phase, nano-scale precipitation phase and atomic-level short-range ordered structure. Under the synergistic effect of multi-level and multi-scale organizations, composite strengthening is achieved, thereby improving the tensile strength of the alloy.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A multi-scale structure composite strengthened high entropy alloy, characterized in that: The high entropy alloy is composed of the elements Co, Cr, Fe, Ni, Nb and Mo. The general formula of the high entropy alloy in terms of atomic ratio is CoCrFeNiNb x Mo 0.4-x , wherein x=0.1-0.3; CoCrFeNiNb x Mo 0.4-x The high entropy alloy includes FCC matrix, micron-scale Laves phase and atomic-scale SRO structure.

2. A method for preparing a multi-scale structure composite reinforced high entropy alloy as claimed in claim 1, characterized in that: The following steps are involved: According to the target atomic ratio, metal particles Co, Cr, Fe, Ni, Nb, and Mo are melted to obtain a cast alloy; The cast alloy is annealed and quenched with water to obtain the multi-scale structure composite reinforced high entropy alloy, wherein the annealing temperature is 600-800°C.

3. The method for preparing a multi-scale structure composite reinforced high entropy alloy according to claim 2, characterized in that: In the step of annealing the cast alloy, the annealing temperature is 700-800°C.

4. The method for preparing a multi-scale structure composite reinforced high entropy alloy according to claim 3, characterized in that: The cast alloy is annealed at 700-800°C to obtain a multi-scale composite strengthened high entropy alloy with a microstructure of FCC matrix, micron-scale Laves phase, nano-scale HCP phase and atomic-scale SRO structure.

5. The method for preparing a multi-scale structure composite reinforced high entropy alloy according to claim 2, characterized in that: Before the step of smelting the metal particles Co, Cr, Fe, Ni, Nb, and Mo, the method further includes the step of deoxidizing the Ti ingot under the protection of an argon atmosphere.

6. The method for preparing a multi-scale structure composite reinforced high entropy alloy according to claim 2, characterized in that: In the step of smelting the metal particles Co, Cr, Fe, Ni, Nb, and Mo, the purity of the metal raw materials is 99.9%.

7. The method for preparing a multi-scale structure composite reinforced high entropy alloy according to claim 2, characterized in that: In the step of smelting the metal particles Co, Cr, Fe, Ni, Nb, and Mo, the smelting is specifically to melt the metal particles into button ingots, turn them over after cooling, and repeat the smelting for more than 5 times.

Citation Information

Patent Citations

  • High-temperature-resistant high-entropy alloy with high room-temperature plasticity and preparation method thereof

    CN114150205A

  • Ultrahigh strength-plasticity matched high-entropy alloy and preparation method thereof

    CN115449691A